2014
DOI: 10.1155/2014/262853
|View full text |Cite
|
Sign up to set email alerts
|

β-Thalassemia Intermedia in Northern Iraq: A Single Center Experience

Abstract: To investigate the molecular basis of β-thalassemia intermedia in Northern Iraq and evaluate its management practices, a total of 74 patients from 51 families were enrolled. The patients were clinically and hematologically reevaluated, and had their β-thalassemia mutations characterized, as well as the number of α-globin genes and Xmn I G γ −158 (C>T) polymorphism studied. Out of 14 β-thalassemia mutations identified, the four most common were IVS-I-6 (T>C) [33.3%], IVS-II-I (G>A) [21.1%], codon 82/83(−G) [10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 35 publications
2
23
6
Order By: Relevance
“…The IVS-I-6 (T→C) mutation is one of the most common causes of β-thalassemia among individuals of Mediterranean and Middle Eastern ancestry [39,40]. Its high incidence has been reported among populations from Portugal [41]; Spain [42,43]; Albania [44]; the region of former Yugoslavia [45,46,47,48]; Greece [49,50,51,52]; Algeria [53]; Egypt [54]; Palestine [55,56]; Lebanon [57]; Syria [58,59]; Cyprus [60]; Turkey [61,62,63,64,65]; Saudi Arabia [66,67]; Iraq [68,69,70,71]; Iran [72,73,74]; and elsewhere. It results from a base substitution close to the 5′ splice junction, between exon I and intron I, and within a conserved consensus sequence, interfering with mRNA splicing and, consequently, reducing its efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The IVS-I-6 (T→C) mutation is one of the most common causes of β-thalassemia among individuals of Mediterranean and Middle Eastern ancestry [39,40]. Its high incidence has been reported among populations from Portugal [41]; Spain [42,43]; Albania [44]; the region of former Yugoslavia [45,46,47,48]; Greece [49,50,51,52]; Algeria [53]; Egypt [54]; Palestine [55,56]; Lebanon [57]; Syria [58,59]; Cyprus [60]; Turkey [61,62,63,64,65]; Saudi Arabia [66,67]; Iraq [68,69,70,71]; Iran [72,73,74]; and elsewhere. It results from a base substitution close to the 5′ splice junction, between exon I and intron I, and within a conserved consensus sequence, interfering with mRNA splicing and, consequently, reducing its efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is an effective applied method for learning, interpreting, and simplifying complicated concepts of thalassemia syndromes. We think that using simple language is most important factor for effectiveness of this course and this method similar case based bedside teaching provides active learning in real context observes students skills, increases learners' motivation and professional thinking, integrates clinical, communication, problem solving, decision making and ethical skills [1][2][3][4][5].…”
Section: Resultsmentioning
confidence: 99%
“…Insulin resistance has been extensively studied among patients with TDT (mainly β‐thalassemia major), and it is known to be related to the severity of iron overload . Meanwhile, studies in NTDT patients (mostly β‐thalassemia intermedia) with iron overload reported variable prevalence of impaired glucose tolerance and DM . However, there are no previous data specific to the role of iron overload in insulin resistance among patients with Hb H disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in adults with NTDT that mainly focused on β‐thalassemia intermedia reported a variable prevalence of impaired glucose tolerance (2.9%‐24%) and DM (1.4%‐4.5%)—both of which were found to be associated with iron overload . However, such studies have been rarely reported in α‐thalassemia hemoglobin H (Hb H) disease, which is the most common form of NTDT worldwide .…”
Section: Introductionmentioning
confidence: 99%